ASEAN trade effect on Pakistan's economic development - Ahmad, Shabbir; Abdul Karim, Noor Al-Huda (2007)
Pakistan began to increase its focus on trade relations with ASEAN member countries in 1990s. The first ASEAN-Pakistan Joint Business Council Meeting held in Karachi in 2000 was an effort to seek measures to enhance trade between Pakistan and ASEAN. This paper examines the possibility that Pakistan’s bilateral trade relationships with ASEAN countries help contribute to its economic development. The analysis covers a period from 1976 to 2005. It uses a panel data on Pakistan’s gross domestic product (GDP) indices (in relative terms) and total trade with each founding member country of ASEAN: namely, Indonesia, Malaysia, Philippines, Singapore and Thailand. Results indicate a positive relationship between the bilateral trade relationships and Pakistan’s economic development. The significance of ASEAN trade effect is better seen in a long-term perspective. It should be realized indirectly through increasing national market size, technology improvements, increase in productivity in economic sectors, growth and expansion of local firms and other economic progresses in Pakistan.